Pembangunan Industri Dengan Sektor Lain - Alif Finno Fidzaky; Verinda Yelanita; Muhammad Yasin (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research examines the interaction between industrial development and other sectors in the economy. The main objective of this research is to identify the impact of industrial development on the agricultural, service and infrastructure sectors and understand the synergies that can be created between sectors. The methodology used includes secondary data analysis from government reports and case studies from several developing countries. The research results show that industrial development has great potential to encourage overall economic growth if it is well integrated with other sectors. Increased productivity in the industrial sector is often followed by growth in the services and infrastructure sectors, but this can lead to imbalances with the agricultural sector if it is not balanced with appropriate policies. This research suggests the need for a holistic approach in development planning that involves all sectors to achieve sustainable economic development.